2012
DOI: 10.1177/0969776411420018
|View full text |Cite
|
Sign up to set email alerts
|

The co-production of purified space: hybrid policing in German Business Improvement Districts

Abstract: Business Improvement Districts (BIDs) have evolved as an ‘innovation’ in urban governance supposed to function as a reaction to inner-city decay, emerging suburbs and the transformation of the retail industry owing to so-called ‘malling’ under ‘actually existing neoliberalism’. In the field of security, the interplay of public police and rent-a-cops being directed by ‘institutionalized lobbyism’ represents local governance regimes in exclusionary action. The paper analyses the concept of BIDs with regard to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
0
35
0
3
Order By: Relevance
“…Eick (2012) draws attention to the way the specifics of the institutional (regulatory, normative and cultural) environment of a place renders a mobile model more or less implementable, changes being made when institutional differences prevent a model being adopted in a form that exists elsewhere (see also Peck and Theodore 2010b). For Faulconbridge (2013), the outcome of mobility is, therefore, often a bricolage process through which a model is made to work in a particular local context.…”
Section: Mutating Modelsmentioning
confidence: 99%
“…Eick (2012) draws attention to the way the specifics of the institutional (regulatory, normative and cultural) environment of a place renders a mobile model more or less implementable, changes being made when institutional differences prevent a model being adopted in a form that exists elsewhere (see also Peck and Theodore 2010b). For Faulconbridge (2013), the outcome of mobility is, therefore, often a bricolage process through which a model is made to work in a particular local context.…”
Section: Mutating Modelsmentioning
confidence: 99%
“…A successful town centre is one where shops are occupied and trade is brisk. In recent literature the high street has been presented as a place of commercial decline and crisis (Hallsworth et al 2010); as a site of economic recovery and reconstruction (Wrigley and Dolega 2011); or as a space to be managed, often with shades of social sanitisation and the exclusion of 'undesirables' through the 'hybrid policing' of private security firms (Eick 2012).…”
Section: From Consumer Rights To Tactical Urbanism: Citizenship In Thmentioning
confidence: 99%
“…They focus on how the institutional environment, of the place receiving the mobile knowledge, determines whether adoption occurs and what types of adaptation this might involve. Studies have shown that combinations of the socio-cultural legitimacy of particular practices (Boxenbaum and Battilana 2005), and the way institutions determine the availability of the skills and supporting infrastructure needed for adoption (Eick 2012), as well as conflicts or synergies with already existing knowledges, practices and regulations (Peck and Theodore 2010), all influence the impacts of knowledge mobilities.…”
Section: Importation Adaptation and The Situating Of Mobile Knowledgesmentioning
confidence: 99%